Mengenal Suku Sakai Lebih Dekat di Museum Sang Nila Utama - Kemala, Annisa; Bunari, Bunari (CV. Rayyan Dwi Bharata, 2025)
The Sang Nila Utama Museum was built in 1975 and operates to this day, storing thousands of collections inside. One of the interesting museum collections is the collection related to the Sakai tribe. The Sakai tribe, which is one of the indigenous tribes in Riau, has unique cultural riches and needs to be preserved. The representation carried out by the Sang Nila Utama museum in the use of preservation and educating visitors about the culture of the Sakai tribe is effective in attracting visitors. In its use, the museum not only functions as a collection storage place, but also as an education center. By studying the Sakai Tribe collection on display, visitors, especially the younger generation, can get to know their ancestral cultural heritage more closely.